2011
DOI: 10.1371/journal.pone.0024767
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Gut Microbiome across Life History of the Malaria Mosquito Anopheles gambiae in Kenya

Abstract: The mosquito gut represents an ecosystem that accommodates a complex, intimately associated microbiome. It is increasingly clear that the gut microbiome influences a wide variety of host traits, such as fitness and immunity. Understanding the microbial community structure and its dynamics across mosquito life is a prerequisite for comprehending the symbiotic relationship between the mosquito and its gut microbial residents. Here we characterized gut bacterial communities across larvae, pupae and adults of Anop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

62
629
15
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 491 publications
(715 citation statements)
references
References 83 publications
62
629
15
2
Order By: Relevance
“…Previous studies mainly focused on noneukaryotic microbes in the midgut using either culture‐dependent or culture‐independent methods (Minard, Mavingui, & Moro, 2013). Those that applied the culture‐independent deep sequencing approach were mainly restricted to gut bacterial communities (Minard et al., 2012; Wang, Gilbreath, Kukutla, Yan, & Xu, 2011) or other isolated adult arthropod parts (Damiani et al., 2010; Sharma et al., 2014), although one study investigated bacteria diversity from whole Ae. albopictus (Minard et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies mainly focused on noneukaryotic microbes in the midgut using either culture‐dependent or culture‐independent methods (Minard, Mavingui, & Moro, 2013). Those that applied the culture‐independent deep sequencing approach were mainly restricted to gut bacterial communities (Minard et al., 2012; Wang, Gilbreath, Kukutla, Yan, & Xu, 2011) or other isolated adult arthropod parts (Damiani et al., 2010; Sharma et al., 2014), although one study investigated bacteria diversity from whole Ae. albopictus (Minard et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a median of 42 bacterial OTUs was estimated from the guts of eight mosquito species (Minard et al., 2012); higher still by at least 200 OTUs was the bacterial richness in the gut of a single adult Anopheles gambiae (Wang et al., 2011). This enormous variability amongst studies, including ours, likely reflects inherent differences in microbiota diversity, composition, and heterogeneity amongst individuals, due to vector species and site of mosquito collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gut transcriptomes of both hematophagous and phytophagous insects have been investigated extensively (Morris et al 2009, Wang et al 2011, Zhang et al 2010, Boissière et al 2012 However, we found it surprising to note the presence of greater sequence diversity in the RWA2 gut library, which shared maximum homology with that of several insect species.…”
Section: Discussionmentioning
confidence: 86%